2017
DOI: 10.1096/fj.201601346r
|View full text |Cite
|
Sign up to set email alerts
|

The role of CB 1 in intestinal permeability and inflammation

Abstract: The endocannabinoid system has previously been shown to play a role in the permeability and inflammatory response of the human gut. The goal of our study was to determine the effects of endogenous anandamide (AEA) and 2-arachidonoyl glycerol (2-AG) on the permeability and inflammatory response of intestinal epithelium under normal, inflammatory, and hypoxic conditions. Human intestinal mucosa was modeled using Caco-2 cells. Human tissue was collected from planned colorectal resections. Accumulation of AEA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…It was reported that endocannabinoid (eCB) system plays a role in gut homeostasis including motility, inflammation and permeability, of which the underlying mechanisms remains to be elucidated ( Lee et al, 2016 ; Karwad et al, 2017 ). CB1 blockage was shown to improve gut barrier function and reduce systemic LPS levels, while the other member of eCB system-CB2 seemed unrelated with permeability ( Muccioli et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that endocannabinoid (eCB) system plays a role in gut homeostasis including motility, inflammation and permeability, of which the underlying mechanisms remains to be elucidated ( Lee et al, 2016 ; Karwad et al, 2017 ). CB1 blockage was shown to improve gut barrier function and reduce systemic LPS levels, while the other member of eCB system-CB2 seemed unrelated with permeability ( Muccioli et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…2C). Further, the report suggested that the increased endogenous AEA enhanced permeability in the Caco-2 cells (45). Therefore, the increase in endogenous AEA could be involved in the cellular phenotype in the NAPE-PLD-deleted cells.…”
Section: Discussionmentioning
confidence: 91%
“…AEA has been shown to play roles in biologic activities, such as cell adhesion and migration, permeability, inflammation, and apoptosis in the in vitro experiments (41)(42)(43)(44)(45). Especially, the inhibitory effect on cell proliferation was exerted by AEA treatment in human colon cancer cell lines (42), implicating a mechanism underlying the slow growth rate of the NAPE-PLD-deleted cells (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In one study, administration of CB2 agonists (JWh133, AM1241) upregulated the CB2 receptors and reduced colonic inflammation in trinitrobenzene sulfonic acid-induced colitis in a murine model [49]. The role of CB1 receptors in inflammation is still under investigation, though some research suggests that they help combat inflammation by modulating the release of other neurotransmitters and producing an "entourage effect" in peripheral nerve terminals [50]. It has been shown that the co-activation of CB1 and CB2 receptors is essential for effective emesis control by endocannabinoids, possibly by blocking the endocannabinoid reuptake by CB2 [51].…”
Section: Mechanism Of Actions Of Endocannabinoidsmentioning
confidence: 99%